2020
DOI: 10.3892/mmr.2020.11161
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the differential expression profile of microRNAs in rats with spinal cord injury treated by electroacupuncture

Abstract: abnormal microrna (mirna) expression has been implicated in spinal cord injury (Sci), but the underlying mechanisms are poorly understood. To observe the effect of electroacupuncture (ea) on mirna expression profiles in Sci rats and investigate the potential mechanisms involved in this process, Sprague-dawley rats were divided into sham, Sci and Sci+ea groups (n=6 each). Basso, Beattie and Bresnahan (BBB) scoring and hematoxylin-eosin staining of cortical tissues were used to evaluate spinal cord recovery with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…For example, miR-21 has been found to play an important role in limiting secondary neuronal apoptosis following an SCI [ 24 ], while Zhou et al [ 33 ] demonstrated that miR-27a can facilitate SCI recovery by regulating the autophagy flux for neuroprotection. Moreover, EA treatment of SCIs in rats induces changes to miRNA expression profiles, as also demonstrated in previous studies [ 34 ]. MiR-106b-5p, a member of the 106b-25 cluster and a paralogue of the 17–92 cluster [ 35 ], has been well-studied in many diseases, including breast cance [ 35 ], and acute renal injury [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…For example, miR-21 has been found to play an important role in limiting secondary neuronal apoptosis following an SCI [ 24 ], while Zhou et al [ 33 ] demonstrated that miR-27a can facilitate SCI recovery by regulating the autophagy flux for neuroprotection. Moreover, EA treatment of SCIs in rats induces changes to miRNA expression profiles, as also demonstrated in previous studies [ 34 ]. MiR-106b-5p, a member of the 106b-25 cluster and a paralogue of the 17–92 cluster [ 35 ], has been well-studied in many diseases, including breast cance [ 35 ], and acute renal injury [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…However, the mechanism underlying the therapeutic effect EA is not well elucidated. A previous study investigated the expression profiles of miRNAs involved in EA-treated SCI rats and demonstrated the potential mechanism and functional role as well as the potential as therapeutic targets of miRNAs in SCI rats [ 56 ]. Studies have also indicated that EA downregulates the expression of miR-449a to increase NSCs proliferation and promote neuron survival [ 17 ].…”
Section: Discussionmentioning
confidence: 99%